2009
DOI: 10.1128/iai.00931-08
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immunity against Capsule Polysaccharide Protects the Host from magA + Klebsiella pneumoniae -Induced Lethal Disease by Evading Toll-Like Receptor 4 Signaling

Abstract: Klebsiella pneumoniae magA (for mucoviscosity-associated gene A) is linked to the pathogenesis of primary pyogenic liver abscess, but the underlying mechanism by which magA increases pathogenicity is not well elucidated. In this study, we investigated the role of the capsular polysaccharides (CPS) in the pathogenesis of magA ؉ K. pneumoniae by comparing host immunity to magA ؉ K. pneumoniae and a ⌬magA mutant. We found that Toll-like receptor 4 recognition by magA ؉ K. pneumoniae was hampered by the mucoviscos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 41 publications
3
40
1
Order By: Relevance
“…All 16 strains analyzed here possessed the mrk and fim operons, coding for fimbrial genes (11,12), and the ent operon, coding for enterobactin (14), consistent with previous results showing that these genes are highly conserved in K. pneumoniae (19,30). None of the isolates demonstrated rmpA and wzy-K1 (magA) genes, which are hypermucoviscosity-associated genes (16,17,19).…”
Section: Species Identification and Antimicrobial Susceptibilitysupporting
confidence: 74%
See 1 more Smart Citation
“…All 16 strains analyzed here possessed the mrk and fim operons, coding for fimbrial genes (11,12), and the ent operon, coding for enterobactin (14), consistent with previous results showing that these genes are highly conserved in K. pneumoniae (19,30). None of the isolates demonstrated rmpA and wzy-K1 (magA) genes, which are hypermucoviscosity-associated genes (16,17,19).…”
Section: Species Identification and Antimicrobial Susceptibilitysupporting
confidence: 74%
“…Capsular types, particularly K1 and K2, and hypermucoviscosity, favored by the positive regulator genes rmpA and rmpA2, are also important for K. pneumoniae virulence. Capsule production increases resistance to phagocytosis and other immune response components (16,17). For detailed descriptions of these and other potential virulence factors of K. pneumoniae, see references 18 and 19. Most of the KPC-producing K. pneumoniae strains isolated worldwide have been attributed to clonal group 258 (CG258) (19,20).…”
mentioning
confidence: 99%
“…Elevated levels of TLR4 on DCs and epithelial cells, acting in a coordinated manner upon K. pneumoniae infection, could thus trigger a powerful immune response. This hypothesis is strengthened by the recent data of Wu et al, who reported that TLR4 is involved in host recognition of K. pneumoniae in macrophage cell lines (46). In their study, the wildtype K. pneumoniae induced downregulation of DC-SIGN.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, it is also involved in virulence properties (46,50), acid stress response (13), osmotic shock (17), and chemotaxis (10). In the present study, a negative role of Fur in CPS biosynthesis that is achieved by the reduction of the RmpA expression is re- ported for the first time.…”
Section: Discussionmentioning
confidence: 63%